2009
DOI: 10.1021/ie900358z
|View full text |Cite
|
Sign up to set email alerts
|

Robust Optimization Model for Crude Oil Scheduling under Uncertainty

Abstract: In this article, a two-stage robust model is proposed to solve the crude oil scheduling problem under uncertain conditions. The first stage of the model is developed using chance-constrained programming and fuzzy programming that can be transformed into the deterministic counterpart problem, whereas the second-stage is scenario-based. Through the combination of the approaches, the two-stage model can deal with uncertain parameters with both continuous and discrete probability distributions within a finite numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…It has been successfully applied to several engineering disciplines including, but not limited to, production (Leung et al, 2007), aeronautical (Du et al, 2000), electronic (Malcolm and Zenios, 1994), mechanical (Li and Azarm, 2008), chemical (Wang and Rong, 2009) and metallurgical engineering (Dulikravich and Egorov-Yegorov, 2005).…”
Section: The Robust Optimization Frameworkmentioning
confidence: 99%
“…It has been successfully applied to several engineering disciplines including, but not limited to, production (Leung et al, 2007), aeronautical (Du et al, 2000), electronic (Malcolm and Zenios, 1994), mechanical (Li and Azarm, 2008), chemical (Wang and Rong, 2009) and metallurgical engineering (Dulikravich and Egorov-Yegorov, 2005).…”
Section: The Robust Optimization Frameworkmentioning
confidence: 99%
“…Despite their complexity, a number of research studies have been reported in the literature. A two-stage model to deal with uncertainties in ship arrival times and demand is presented in [11]. Their work integrates chance-constrained programming and fuzzy programming in the first stage to develop a model that can be transformed into a deterministic counterpart and employ a scenario-based framework in the second stage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the uncertainties present in the system as a result of technological factors and, economical factors as well as the uncertainty in the mathematical model and parameters employed to perform the optimization task pose severe challenges. A number of publications concerning optimization under uncertainty are available, covering a range of topics, such as process synthesis, design and control under uncertainty (Acevedo & Pistikopoulos (1996); Pintarič & Kravanja (2008); Ricardez-Sandoval, Douglas, & Budman (2011)), planning under uncertainty (Hansen, Grunow, & Gani, 2011), uncertainty on scheduling (Wang & Rong, 2010), strategic and global supply chain networks (Verderame & Floudas (2011); You & Grossmann (2008)), etc. Most of those publications, when addressing the uncertainty of the optimization problem, have focused on the operational parameters and external sources of uncertainties, for example, product demand and uncertainty on raw material availability.…”
Section: Introductionmentioning
confidence: 99%